2020
DOI: 10.3389/fcell.2020.00076
|View full text |Cite
|
Sign up to set email alerts
|

RANKL/RANK System-Based Mechanism for Breast Cancer Bone Metastasis and Related Therapeutic Strategies

Abstract: Breast cancer remains one of the most life-threatening tumors affecting women. Most patients with advanced breast cancer eventually develop metastatic diseases, which cause significant morbidity and mortality. Approximately two-thirds of patients with advanced breast cancer exhibit osteolytic-type bone metastasis, which seriously reduce the quality of life. Therefore, development of novel therapeutic strategies for treating breast cancer patients with bone metastasis is urgently required. The "seed and soil" t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 107 publications
(117 reference statements)
0
52
0
2
Order By: Relevance
“…Breast cancer cells can also produce RANKL and normal cells in metastatic sites, such as osteoblasts in bone [ 30 , 40 , 41 , 42 , 43 ]. RANKL has also been reported to trigger the migration of human epithelial cancer and melanoma cells expressing RANK in a concentration-dependent manner, thus implying a chemotactic mechanism of action in bones [ 30 ].…”
Section: Role Of Rankl In the Survival Resistance Development Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer cells can also produce RANKL and normal cells in metastatic sites, such as osteoblasts in bone [ 30 , 40 , 41 , 42 , 43 ]. RANKL has also been reported to trigger the migration of human epithelial cancer and melanoma cells expressing RANK in a concentration-dependent manner, thus implying a chemotactic mechanism of action in bones [ 30 ].…”
Section: Role Of Rankl In the Survival Resistance Development Andmentioning
confidence: 99%
“…Osteoclastic resorption results in an increased release of transforming growth factor (TGF-β) and other factors of the bone matrix, promoting the increased proliferation of cancer cells. A vicious cycle is thus established promoting bone destruction and metastasis [ 42 , 45 , 48 ].…”
Section: Role Of Rankl In the Survival Resistance Development Andmentioning
confidence: 99%
“…Recently, the RANK/RANKL/OPG system has been observed to play a key role in tumor cell migration and invasion [7][8][9]. Studies have shown that TNFRSF11(RANK) is expressed in a variety of tumor tissues, such as osteosarcoma [10,11], chondrosarcoma [12], breast cancer [13], prostate cancer [14,15], renal cancer [16], oral squamous cell carcinoma [17], lung cancer [18], thyroid cancer [19], and melanoma [20]. However, the expression of TNFRSF11 in gastric cancer cells is rarely reported, and there is no report on the relationship between TNFRSF11 gene polymorphism and gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 There is a significant interplay with the immune system and cytokine release, leading to bone remodeling and metabolism centered around RANK/RANKL, mTOR (mammalian target of rapamycin) and others (IL-33/IL31). 18,[24][25][26][27] Scagliotti et al…”
Section: Discussionmentioning
confidence: 99%